Español - Español, Español; Español, Español; Español, Español (Ars Pharmaceutica (Internet), 1991)
A greenhouse experiment was carried out to determine the capacity of three different composts to release boron gradually to a ryegrass crop. The three composts were made up using the following agricultural wastes: compost BO: 75% sugarcane bagasse, 17% orugo cake and 8% hen manure; compost BG: 78% bagas se and 22% hen manure and compost BT: 95% bagasse and 5% tobacco dust. The composts made up of sugarcane bagasse plus tobacco dust was more effective in releasing boron to the plant than bagasse mixed with orugo and/or hen manure composts. With respect to the form of B release, compost BO did it gradually, compost BG after a long period of integration in the soil and compost BT immediately, during the initial phase of the experiment.